Relevancy of positive trends in mortality and functional recovery after surgical treatment of acute subdural hematomas. Our 10-year experience. (2nd January 2017) - Lenzi, Jacopo; Caporlingua, Federico; Caporlingua, Alessandro; Anichini, Giulio; Nardone, Antonio; Passacantilli, Emiliano; Santoro, Antonio
Abstract: Background: Among traumatic brain injuries, acute subdural hematoma (aSDH) is considered one of the most devastating still retaining poor surgical outcomes in a considerable percentage of affected patients. However, according to results drawn from published samples of aSDH patients, overall mortality and functional recovery have been progressively ameliorating during the last decades. Methods: We present a retrospective analysis of 316 consecutive cases of post-traumatic aSDH operated on between 2003 and 2011 at our institution. Results: Mortality was 67% ( n = 212); a useful recovery was achieved in 16.4% cases ( n = 52). Age >65 years, a preoperative Glasgow coma scale (GCS) ≤ 8, specific pre-existing medical comorbidities (hypertension, heart diseases) were found to be strong indicators of unfavorable outcomes and death during hospitalization. Conclusion: Our results, compared with those of the inherent literature, led the authors to question both the "aggressiveness" of neurosurgical care indications in certain subpopulations of patients being known to fare worse or even die regardless of the treatment administered and the relevance of the results concerning mortality and functional recovery reported by third authors.